Ethanolic Peel Extract Attenuates Isonazid-induced Hepatic Injury in Rats via Reduced NF-kB, and Caspase 3 Expression - Triyanta Yuli Pramana; Thomas Nata Nugraha; Brian Wasita; Eti Poncorini Pamungkasari (Poltekkes Kemenkes Surabaya, 2026)
Isoniazid can induce hepatotoxicity and liver fibrosis via oxidative stress, NF-κB, and caspase-3 pathways. Garcinia mangostana L. (mangosteen) peel extract, rich in xanthones, offers anti-inflammatory and anti-apoptotic properties that may mitigate drug-induced liver injury. To evaluate the effects of mangosteen peel ethanol extract on NF-κB p65, caspase-3 expression, and hepatic fibrosis in isoniazid-treated Wistar rats. In this experimental study, 28 male Wistar rats were divided into four groups: negative control (NC), positive control (PC; isoniazid 50 mg/kg), and two treatment groups receiving isoniazid plus mangosteen extract at 250 mg/kg (I1) and 500 mg/kg (I2) for 30 days. Liver tissues were analyzed using immunohistochemistry (NF-κB, caspase-3) and Masson’s trichrome staining (fibrosis). The 500 mg/kg dose significantly reduced NF-κB p65 and caspase-3 expression and mitigated hepatic fibrosis compared to the PC group (p < 0.05). The 250 mg/kg dose showed less pronounced effects. Garcinia mangostana L. peel extract, especially at 500 mg/kg, effectively attenuates isoniazid-induced liver injury by downregulating NF-κB and caspase-3 in isoniazid-induced Wistar rats. These findings suggest its potential as an adjunct in preventing isoniazid-induced hepatic injury in a preclinical setting. Additional translational and clinical investigations are needed to determine its efficacy and safety as a potential hepatoprotective agent in humans.